2019
DOI: 10.1128/jcm.01537-18
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Sharing of Klebsiella pneumoniae Strains between Healthy Companion Animals and Cohabiting Humans

Abstract: This study aimed to characterize the fecal colonization and sharing of Klebsiella pneumoniae strains between companion animals and humans living in close contact. Fecal samples were collected from 50 healthy participants (24 humans, 18 dogs, and 8 cats) belonging to 18 households. Samples were plated onto MacConkey agar (MCK) plates with and without cefotaxime or meropenem supplementation. Up to five K. pneumoniae colonies per participant were compared by pulsed-field gel electrophoresis (PFGE) after XbaI rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 44 publications
9
55
0
1
Order By: Relevance
“…In our study, K. pneumoniae was found in 0.0–31.3% (mean 17.2%) of stool samples tested. This is lower than in previous studies with a colonization rate of 37.5% ( Marques et al, 2019 ) and 55.9% ( Huynh et al, 2020 ) but is in concordance with other studies reporting 4–10% colonization rates for test subjects ( Choby et al, 2020 ). In contrast to other studies, where an increased fecal carriage rate during the summer was reported ( Anderson et al, 2008 ), no such seasonal correlation could be observed in our study.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, K. pneumoniae was found in 0.0–31.3% (mean 17.2%) of stool samples tested. This is lower than in previous studies with a colonization rate of 37.5% ( Marques et al, 2019 ) and 55.9% ( Huynh et al, 2020 ) but is in concordance with other studies reporting 4–10% colonization rates for test subjects ( Choby et al, 2020 ). In contrast to other studies, where an increased fecal carriage rate during the summer was reported ( Anderson et al, 2008 ), no such seasonal correlation could be observed in our study.…”
Section: Discussionsupporting
confidence: 88%
“…By contrast, the K. pneumoniae ST17 background that has frequently been identified here is a clonal type frequently found among clinical isolates recovered from Portuguese patients [ 24 ]. This ST was also identified in other countries [ 37 ], and not only among hospitalized patients but also in healthy individuals and companion animals [ 38 ].…”
Section: Discussionmentioning
confidence: 55%
“…Colonization was also described worldwide, with rates ranging from 6% to 24% in different geographical regions and different cohorts [ 11 , 12 , 13 , 14 ]. Recent studies described co-carriage of ESBL producing Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae) strains in humans and dogs of the same household [ 15 , 16 ]. These findings highlight the importance of investigating shedding rates and risk factors for shedding by dogs and cats in both veterinary and ‘one health’ perspectives.…”
Section: Introductionmentioning
confidence: 99%